Locomotor and respiratory muscle abnormalities in HFrEF and HFpEF - Mangner, Norman; Winzer, Ephraim B.; Linke, Axel; Adams, Volker (Frontiers in Cardiovascular Medicine, 2023)
Heart failure (HF) is a chronic and progressive syndrome affecting worldwide billions of patients. Exercise intolerance and early fatigue are hallmarks of HF patients either with a reduced (HFrEF) or a preserved (HFpEF) ejection fraction. Alterations of the skeletal muscle contribute to exercise intolerance in HF. This review will provide a contemporary summary of the clinical and molecular alterations currently known to occur in the skeletal muscles of both HFrEF and HFpEF, and thereby differentiate the effects on limb and respiratory muscles, in particular the diaphragm. Moreover, current and future therapeutic options to address skeletal muscle weakness will be discussed focusing mainly on the effects of exercise training.